Analysis of Curved Steel Girder Bridges - Lavelle, Francis H. (Engineering Journal, 1966)
In recent years, with the introduction of highway interchanges in cities, a demand for curved bridges has developed. A typical city interchange is one proposed for Interstate Highway 95 in Providence, R. I., for which most of the ramps are on structure. Steel girder bridges are a good solution to this type of problem. Many such horizontally curved bridges have been built, but generally the steel girders have been straight. However, if one knew with reasonable certainty how to design curved steel girders, there would be definite advantages.